2021
DOI: 10.3390/pathogens10040394
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Highly Pathogenic A/H5Nx (Clade 2.3.4.4) Influenza Viruses in the Sera of Vietnamese Residents

Abstract: To cause a pandemic, an influenza virus has to overcome two main barriers. First, the virus has to be antigenically new to humans. Second, the virus has to be directly transmitted from humans to humans. Thus, if the avian influenza virus is able to pass the second barrier, it could cause a pandemic, since there is no immunity to avian influenza in the human population. To determine whether the adaptation process is ongoing, analyses of human sera could be conducted in populations inhabiting regions where pande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…The antigenic characterization assay described by the Centres for Disease Control and Prevention (CDC) suggest that influenza viruses are likely to be antigenically dissimilar if their HI titres vary by five or more fold ( https://www.cdc.gov/flu/about/professionals/antigenic.htm ). Our HI results were highly consistent with previous studies, indicating that H5 HPAIVs from the clade 2.3.4.4 exhibit considerable antigenic variation [ 57–59 ]. Both A/wildDuck/MN/H5N6/2018-19 HPAIVs from subclade 2.3.4.4h were antigenically distinct from H5 HPAIVs from clades 0 and 2.3.4.4e and c, suggesting the development of candidate vaccines for H5 HPAIVs subclade 2.3.4.4h are needed.…”
Section: Discussionsupporting
confidence: 92%
“…The antigenic characterization assay described by the Centres for Disease Control and Prevention (CDC) suggest that influenza viruses are likely to be antigenically dissimilar if their HI titres vary by five or more fold ( https://www.cdc.gov/flu/about/professionals/antigenic.htm ). Our HI results were highly consistent with previous studies, indicating that H5 HPAIVs from the clade 2.3.4.4 exhibit considerable antigenic variation [ 57–59 ]. Both A/wildDuck/MN/H5N6/2018-19 HPAIVs from subclade 2.3.4.4h were antigenically distinct from H5 HPAIVs from clades 0 and 2.3.4.4e and c, suggesting the development of candidate vaccines for H5 HPAIVs subclade 2.3.4.4h are needed.…”
Section: Discussionsupporting
confidence: 92%
“…In the case of the influenza virus, the countries of Southeast Asia are recognized as the hot spots for the emergence of viruses with epidemic and pandemic potentials [18]. Indeed, we have demonstrated that among 295 serum samples from healthy donors, collected in Vietnam in 2017-2018, 22% were positive in HI-tests and 16% were positive in MN for A/H5Nx viruses [19]. Since the East Asian-Australasian Flyway connects Vietnam and other Southeast Asian countries with Russia, the variants of the influenza virus with pandemic potential can be assumed to enter the Siberian and Far Eastern regions of Russia by migratory birds and further evolve independently.…”
Section: Discussionmentioning
confidence: 89%
“…To date, 42 cases of human infection with influenza A(H5N6) 2.3.4.4 viruses have been reported, 22 of which resulting in death [ 7 , 9 , 10 ]. Moreover, antibodies against 2.3.4.4 viruses were found in the sera of many residents during the 2017−2018 H5 HPAI outbreak in Vietnam [ 11 ]. Taken together, these results strongly suggest that viruses causing poultry outbreaks can also cause human H5 HPAI cases.…”
Section: Introductionmentioning
confidence: 99%